Diffusion-Weighted MR Imaging Lesions after Filter-Protected Stenting of High-Grade Symptomatic Carotid Artery Stenoses - du Mesnil de Rochemont, R.; Schneider, S.; Yan, B.; Lehr, A.; Sitzer, M.; Berkefeld, J. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE:The clinical efficacy of filter devices in internal carotid artery (ICA) stent placement has been a matter of controversy. The aim of this retrospective study was to assess the number and extent of cerebral emboli, as represented by new lesions on diffusion-weighted MR imaging (DWI), in patients treated with filter-protected carotid stent placement.METHODS:Standard DWI (B0 = 1000) was performed within 48 hours before and 48 hours after filter-protected carotid stent placement in 50 patients with symptomatic, high grade (>70%), atherosclerotic ICA stenosis. Number, extent, and vascular territory of new DWI lesions after stent placement were assessed by consensus of 2 experienced neuroradiologists. Multifactorial statistical analysis was performed to determine risk factors associated with DWI lesions.RESULTS:New punctate DWI lesions with a median diameter of 2 mm were detected in 14 of 50 cases in the territory of the stented ICA and in 7 of 50 cases in other vascular territories. Median lesion load was 1 lesion (range, 1–15) per positive case in the stented ICA and 1 lesion (range, 1–7) in other vascular territories. All DWI lesions were clinically asymptomatic. Because of 1 hyperperfusion syndrome with temporary brain swelling, the 30-day stroke and death rate was 2%. Age ≥70 years was the only significant predictor for new DWI lesions, whereas sex, degree and site of stenosis, vascular risk factors, and stent and filter type showed no significant correlation.CONCLUSIONS: New DWI lesions after filter-protected carotid stent placement are substantially more frequent in the ipsilateral ICA territory compared with other vascular territories. Therefore, intraluminal filters cannot completely protect the brain from procedure-related embolization. However, individual lesion load and the risk of clinically relevant ischemia is low.